2006
DOI: 10.5694/j.1326-5377.2006.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Sideswipe injuries to the elbow in Western Australia

Abstract: Objective: To examine the conditions leading to sideswipe injury of the upper limb in motor vehicle accidents and to highlight the severity of these injuries. Design and setting: Prospective study of upper‐limb sideswipe injuries in patients admitted to Royal Perth Hospital, Western Australia, between August 2003 and January 2005. Participants: Eleven patients sustaining sideswipe injuries to the upper limb. Main outcome measures: Accident pattern, type of injury, surgical management, complications, and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Of the 53 studies, 33 had a prospective cohort design, 13 were retrospective studies, and 7 studies had a cross-sectional design. The sample size varied from 11 [ 45 ] to 32,970 [ 30 ] participants. Most studies were conducted in Europe ( n = 22, 42%), followed by Australia ( n = 17, 30%), North America ( n = 10, 19%), South America ( n = 2 Brazil and Chile, 4%), Africa ( n = 1 Uganda, 2%) and the Middle East ( n = 1 Israel, 2%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 53 studies, 33 had a prospective cohort design, 13 were retrospective studies, and 7 studies had a cross-sectional design. The sample size varied from 11 [ 45 ] to 32,970 [ 30 ] participants. Most studies were conducted in Europe ( n = 22, 42%), followed by Australia ( n = 17, 30%), North America ( n = 10, 19%), South America ( n = 2 Brazil and Chile, 4%), Africa ( n = 1 Uganda, 2%) and the Middle East ( n = 1 Israel, 2%).…”
Section: Resultsmentioning
confidence: 99%
“…Kinzel et al reported on 10 cases of side swipe injuries of the elbow that were treated by primary open reduction and internal fixation of the humerus, radius and ulna, nine of them needed additional surgical procedures. Eight patients had extensive functional deficit (9). …”
Section: Discussionmentioning
confidence: 99%
“…3 The massive trauma to the elbow is characterized by involvement of all the major tissues including bones, joints, vessels, nerves, muscles, and skin which require demanding surgical management with high level of expertise. 4 5 6 7 8 After primary repair, secondary reconstruction of elbow is often required due to loss of bone and muscles around the elbow resulting in instability with functional loss, associated with or without pain, provided the neurovascular status of the limb is reasonably preserved. To ensure the stability of the elbow either arthrodesis or its prosthetic replacement may be contemplated.…”
Section: Introductionmentioning
confidence: 99%
“…Other options like interposition arthroplasties are also difficult to contemplate around the deficient bone ends. Except sporadic case report of prosthetic replacement of elbow in side swipe injuries, 8 9 10 11 no report on a series of such cases and their functional results have been published in the literature within our knowledge. The object of this paper is to report the long term functional results of Baksi sloppy hinge elbow arthroplasty in a series of such patients.…”
Section: Introductionmentioning
confidence: 99%